Performance management - Hutchinson, Sue (London Chartered Institute of Personnel and Development, 2013)
'Performance Management' is an essential core text for any student taking a performance management module at undergraduate or postgraduate level.
Chapter 1 Setting the Scene: HRM and Performance -- Chapter 2 Strategic Performance Management -- Chapter 3 Motivation at Work -- Chapter 4 The Role of Line Managers in Managing Performance -- Chapter 5 Defining and Measuring Individual Work Performance -- Chapter 6 Performance Appraisal and Feedback -- Chapter 7 Integrating Learning and Performance -- Chapter 8 Performance-related Rewards -- Chapter 9 Managing Under-Performance -- Chapter 10 Absence Management -- Chapter 11 International Performance Management -- Chapter 12 Developing Performance Management.
Keywords: Performance -- Management .; Employees -- Rating of .; Performance standards